Vacancy Duration and Wages - Ihsaan Bassier; Alan Manning; Barbara Petrongolo (Institute of Labor Economics (IZA), 2023)
We estimate the elasticity of vacancy duration with respect to posted wages, using data from the near-universe of online job adverts in the United Kingdom. Our research design identifies duration elasticities by leveraging firm-level wage policies that are plausibly exogenous to hiring difficulties on specific job vacancies, and control for job and market-level fixed-effects. Wage policies are defined based on external information on pay settlements, or on sharp, internally-defined, firm-level changes. In our preferred specifications, we estimate duration elasticities in the range -3 to -5, which are substantially larger than the few existing estimates.
Keywords: J42; J63; J64; 330; vacancy duration; monopsony; wages